Factors influencing the success and complications of intraosseous access in pediatric patients—a prospective nationwide surveillance study in Germany - Pfeiffer, Daniel; Olivieri, Martin; Brenner, Sebastian; Gomes, Delphina; Lieftüchter, Victoria; Hoffmann, Florian (Frontiers in Pediatrics, 2023)
Background: Vascular access is essential for the efficient treatment of critically ill children, but it can be difficult to obtain. Our study was conducted to analyze the feasibility and shortterm safety of intraosseous access (IO) use as well as factors influencing its success and the incidence of complications in pediatric emergencies and resuscitation. This dataset of systematically documented intraosseous access attempts constitutes one of the largest published in the literature.Methods: Two-year nationwide prospective surveillance study in Germany from July 2017 to June 2019. Pediatric hospitals anonymously reported the case data of all children aged 28 days to 18 years who arrived with or were treated with an intraosseous access to the German Pediatric Surveillance Unit (GPSU). The main outcomes were the occurrence of complications, overall success and success at the first attempt. The influence of individual factors on outcomes was evaluated using multivariate regression models. Results: A total of 417 patients underwent 549 intraosseous access attempts. The overall rates of success and success at the first attempt were 98.3% and 81.9%, respectively.Approximately 63.6% of patients were successfully punctured within 3 minutes from the time of indication. Approximately 47.7% of IO access attempts required patient resuscitation.Dislocation [OR 17.74 (5.32, 59.15)] and other complications [OR 9.29 (2.65, 32.55)] occurred more frequently in the prehospital environment. A total of 22.7% of patients experienced minor complications, while 2.5% of patients experienced potentially severe complications. Conclusion: We conclude that intraosseous access is a commonly used method for establishing emergency vascular access in children, being associated with a low (age-dependent) rate of severe complications and providing mostly reliable vascular access despite a relatively high rate of dislocation.